Integrating support verb constructions into a parser - Rassi, Amanda; Baptista, Jorge; Mamede, Nuno; Vale, Oto (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2015: Anais do X Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2015)
This paper describes the process of integrating into a rule-based parser a set of approximately 1,000 nominal predicates forming support verb constructions (SVC) with the verb dar 'give' in Brazilian Portuguese. The system was evaluated on a sample of 580 sentences containing verb-noun combinations candidates to SVC, manually and independently annotated. Best results yield 85% precision, 79% recall, 76% accuracy and 82% F-measure.